ADOPTION OF TARGET COSTING PRACTICES BY INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) SERVICE COMPANIES - Cortes Braga, Eliane (Management Control Review, 2022)
This research aims to investigate the adoption of practices of the target costing process by companies in the ICT services sector – Information and Communication Technology. For this, a literature review was carried out on target costing – concept, objective, principles and stages of its process. A survey was carried out, using a standardized and structured online questionnaire, with companies associated with ASSESPRO (Associations of Brazilian Information Technology Companies). Data were analyzed using descriptive statistics. The results found show that the participating companies are small and medium-sized companies with low organizational complexity. Overall, the findings show that the investigated companies make use of practices of the target costing process, especially practices of the initial stages of the process: stage of defining the characteristics of products/services and the stage of defining the profit margin and estimating the cost target of products/services. Although the practices of the following stages of the target costing process (cost management activities and continuous improvement activities) also show high frequency numbers, the results suggest that the investigated companies need to improve in this aspect.